THE TRANSFORMATION OF MEDAN POST OFFICE: FROM POSTAL SERVICE TO CREATIVE CULTURAL CENTER - Hana Maulida Rangkuti; Faizaturrahmah; Fadhla Hayati; Ikhwan Yazid H (PT. Radja Intercontinental Publishing, 2025)
The Medan Post Office is a colonial heritage building that has undergone a functional transformation into a creative space called Pos Bloc Medan. This study aims to describe the transformation process of the Medan Post Office's function within the context of preserving its historical value as a cultural heritage building. The research method used a descriptive qualitative approach through a literature review of various journals and books. The results show that this transformation reflects the application of the adaptive reuse concept, which is able to maintain the value of colonial architecture while providing new functions relevant to the social, cultural, and economic needs of today's society.